Residential culturable fungi, (1‐3, 1‐6)‐β‐d‐glucan, and ergosterol concentrations in dust are not associated with asthma, rhinitis, or eczema diagnoses in children. (24th October 2013) - Choi, H.; Byrne, S.; Larsen, L. S.; Sigsgaard, T.; Thorne, P. S.; Larsson, L.; Sebastian, A.; Bornehag, C.‐G.
Abstract Qualitative reporting of home indoor moisture problems predicts respiratory diseases. However, causal agents underlying such qualitative markers remain unknown. In the homes of 198 multiple allergic case children and 202 controls in Sweden, we cultivated culturable fungi by directly plating dust, and quantified (1‐3, 1‐6)‐β‐d‐glucan and ergosterol in dust samples from the child's bedroom. We examined the relationship between these fungal agents and degree of parent or inspector‐reported home indoor dampness, and microbiological laboratory's mold index. We also compared the concentrations of these agents between multiple allergic cases and healthy controls, as well as IgE‐sensitization among cases. The concentrations of culturable fungal agents were comparable between houses with parent and inspector‐reported mold issues and those without. There were no differences in concentrations of the individual or the total summed culturable fungi, (1‐3, 1‐6)‐β‐d‐glucan, and ergosterol between the controls and the multiple allergic case children, or individual diagnosis of asthma, rhinitis, or eczema. Culturable fungi, (1‐3, 1‐6)‐β‐d‐glucan, and ergosterol in dust were not associated with qualitative markers of indoor dampness or mold or indoor humidity. Furthermore, these agents in dust samples were not associated with any health outcomes in the children.